T Cells of Atopic Asthmatics Preferentially Infiltrate Into Human Bronchial Xenografts in SCID Mice - Tsumori, Kaori; Kohrogi, Hirotsugu; Goto, Eisuke; Hirata, Naomi; Hirosako, Susumu; Fujii, Kazuhiko; Ando, Makoto; Kawano, Osamu; Mizuta, Hiroshi (The Journal of immunology (1950), 2003)
T cells play an important role in the pathogenesis of bronchial asthma. However, it is not completely known how circulating lymphocytes infiltrate into the airways of asthmatic patients. Because SCID mice are unable to reject xenogenic transplants, many xenotransplant models using various human tissues have been developed. Therefore, to examine the interaction between bronchi and T lymphocytes of asthma, it may be possible to use the human bronchial xenograft and PBMC xenograft in SCID mice. We transplanted human bronchi into the subcutaneum of SCID mice and i.p. injected PBMCs that were obtained from patients with atopic asthma, atopic dermatitis and rheumatoid arthritis, and normal subjects (asthmatic, dermatitis, rheumatic, and normal huPBMC-SCID mice). There was no difference in the percentage of CD3-, CD4-, CD8-, CD25-, CD45RO-, CD103-, and cutaneous lymphocyte Ag-positive cells in PBMCs among the patients with asthma, dermatitis, rheumatoid arthritis, and normal subjects, and CD3-positive cells in peripheral blood of asthmatic, dermatitis, rheumatic, and normal huPBMC-SCID mice. The number of CD3-, CD4-, and CD8-positive cells in the xenografts of asthmatic huPBMC-SCID mice was higher than those of dermatitis, rheumatic, and normal huPBMC-SCID mice. IL-4 mRNA and IL-5 mRNA were significantly higher in the xenografts of asthmatic huPBMC-SCID mice than those in the xenografts of normal huPBMC-SCID mice, but there were no significant differences in the expressions of IL-2 mRNA or IFN-γ mRNA between them. These findings suggest that T cells, especially Th2-type T cells, of asthmatics preferentially infiltrate into the human bronchi.